Resolving the African leadership challenge : insight from history - Amah, Okechukwu Ethelbert (Emerald Publishing Limited, 2023)
Resolving the African Leadership Challenge: Insight From History examines leadership in pre-colonial, colonial and postcolonial modern Africa, exploring the origin of Africa's leadership challenge, and providing lessons to enhance leadership effectiveness. New ground is broken here as the author examines: The breadth of leadership issues across the entire continent The evolution of issues over time; from the pre-colonial era to the modern day The practical lessons that can be identified to resolve the leadership challenge A clear roadmap to achieve better leadership in Africa This interdisciplinary study provides a deeper understanding of the history of leadership in Africa, giving us key principles for today. It is essential reading for academic researchers, postgraduate students, and practitioners, seeking to adapt leadership theories to real-world local practice.